Carotid body, insulin, and metabolic diseases: unraveling the links - Conde, Sílvia V.; Sacramento, Joana F.; Guarino, Maria P.; Gonzalez, Constancio; Obeso, Ana; Diogo, Lucilia N.; Monteiro, Emilia C.; Ribeiro, Maria J. (Frontiers in Physiology, 2014)
The carotid bodies (CB) are peripheral chemoreceptors that sense changes in arterial blood O2, CO2 and pH levels. Hypoxia, hypercapnia and acidosis activate the CB, which respond by increasing the action potential frequency in their sensory nerve, the carotid sinus nerve (CSN). CSN activity is integrated in the brain stem to induce a panoply of cardiorespiratory reflexes aimed, primarily, to normalize the altered blood gases, via hyperventilation, and to regulate blood pressure and cardiac performance, via sympathetic nervous system (SNS) activation. Besides its role in the cardiorespiratory control the CB has been proposed as a metabolic sensor implicated in the control of energy homeostasis and, more recently, in the regulation of whole body insulin sensitivity. Hypercaloric diets cause CB overactivation in rats, which seems to be at the origin of the development of insulin resistance and hypertension, core features of metabolic syndrome and type 2 diabetes. Consistent with this notion, CB sensory denervation prevents metabolic and hemodynamic alterations in hypercaloric feed animal. Obstructive sleep apnoea (OSA) is another chronic disorder characterized by increased CB activity and intimately related with several metabolic and cardiovascular abnormalities. In this manuscript we review in a concise manner the putative pathways linking CB chemoreceptors deregulation with the pathogenesis of insulin resistance and arterial hypertension. Also, the link between chronic intermittent hypoxia (CIH) and insulin resistance is discussed. Then, a final section is devoted to debate strategies to reduce CB activity and its use for prevention and therapeutics of metabolic diseases with an emphasis on new exciting research in the modulation of bioelectronic signals, likely to be central in the future.